Exploring numerical approaches for pre-test progressive collapse assessment of RC frame structures. (15th December 2019) - Koh, Yong Hong; Krauthammer, Theodor
Highlights: Compared collapse simulations for connection models in a RC structure with test data. Abstract: Finite element (FE) codes can be used for the assessment of progressive collapse of building structures. However, the effectiveness and accuracy of such simulations is highly dependent on the accuracy of modeling the structural systems and their connections. A four-story full-scale reinforced concrete structural frame was selected for the present study. The structure was tested by other investigators for assessing its progressive collapse behavior, and the results were published after this study had been completed. A predominantly continuum based FE model was developed in this study for the structural system that addressed the effect of beams and slab on the load resistance of the connections. A load resistance function of the connections was derived, as a basis for a fast-running FE model, to simulate the behavior of such connections. This simplified FE approach was validated by simulating connection details that were tested by other investigators, and it produced very similar results with significant time saving, as compared to full 3D FE simulations, for the same connection test specimens. It enabled one to obtain reasonable estimates of the load-rotation function of the interior connection at a much-reduced computational time. Therefore, the simplified approach was used for the progressive collapse assessment of the tested structural system, and the obtained results were compared with test data.